# Question: Find the Laplace transform of the function f t te a t 1 g t 1 3202

Find the Laplace transform of the function

f(t) = te-a(t-1)g(t-1)

f(t) = te-a(t-1)g(t-1)

## Relevant Questions

if f (t) = e-at cos(ωt) show F(s) = s + a / (s + a)2 + (ω)2Use the shifting Theorem to determine L{f(t)} where f(t) = [e-(t-2) – e –(t-1)]u(t-1)A screw clamp similar to the one shown in the figure has a handle with diameter 3/16 in made of cold-drawn AISI 1006 steel. The overall length is 3 in. The screw is 7/16 in-14 UNC and is 5 ¾ in long, overall. Distance A is ...A ¾ in-16 UNF series SAE grade 5 bolt has a ¾ -in ID tube 13 in long, clamped between washer faces of bolt and nut by turning the nut snug and adding one-third of a turn. The tube OD is the washer-face diameter dw = 1.5d = ...The same as Prob. 8–24, except that ½ -in cap screws are used with washers (see Fig. 8–21).Post your question